Lessons Learned and New Challenges: Re-evaluation of End-User Assessment of a Skills-Based Training Program for Urology Trainees. (March 2019) - Flanders, Damian; Pirpiris, Athina; Corcoran, Niall; Forsyth, Robert; Grills, Richard
Objectives: To re-assess the perceived benefit and relevance of simulation sessions to Victorian urology trainees and to identify areas for potential improvement. Subjects and methods: All trainees attending skills training sessions between 2011 and 2016 were asked to complete a structured questionnaire at the completion of the session. The questionnaire included 11 topic areas ranging from the year of surgical training to degree of usefulness of the session, including several sections for free-text response to offer more detailed feedback. Sessions were examined both individually and collectively to assess end-user satisfaction with the structure and content of the program. Results: In total, 24 individual skills sessions were held over the 6-year period, with a total of 355 attendees. Of these, 331 attendees completed the majority of the questionnaire, a response rate of over 93%. Overall 88% of the surveyed attendees stated that they had both the support of their supervising consultant and the flexibility of workload to attend the session; 90% of trainees felt that there was adequate reading material provided prior to the skills session, an improvement from 76% in the previous study period; and 97% of those surveyed felt that the existing session structure was appropriate and the same proportion found the sessions both useful and interesting, compared with just 63% in the previous study period. Analysis of individual topics demonstrates some variability in outcome measures, but for nearly every assessed parameter, greater than 90% of participants agreed that the session fulfilled the expected criteria. New topics developed since the 2011 analysis, including renal transplant and vascular repair, also had high levels of satisfaction. The practical models used have been refined and achieved higher scores than those in the previous assessment period. Conclusion: The urology skills-based training program has been well received by the surveyed trainees and is now embedded and accepted as part of the Victorian training program. The format of the sessions has matured and the overall rating, both individually and collectively, was high. There has been a clear increase in satisfaction across most areas assessed when compared with previous feedback. Despite this, there remain areas that can be improved, such as the amount and quality of available equipment and the inclusion of video demonstrations of operative techniques.